ANALISIS KONDISI INDEKS KUALITAS AIR PADA ENAM MATA AIR DI KABUPATEN GIANYAR, BALI - I Wayan Gde Samping Gargitha; I Wayan Restu; Alfi Hermawati Waskita Sari (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Spring is the source of water that occurs naturally. This research aim was to investigate the water quality status of six springs in Gianyar regency based on water quality index.This research was conducted in January 2016 at Taman Sari Spring, Tirta Sudamala Spring, Beji Kengetan Spring, Gerembeng Kengetan Spring, Rijasa Spring and Beji Jeleka Spring. The samples were taken using purposive sampling method and analyzed using descriptive quantitative. The value of water quality index determine using 9 parameters, such as temparature changes, turbidity, total dissolved solid, pH, dissolved oxygen, biological oxygen demand, nitrate, phosphate and faecal coliform bacteria. The results of water quality index showing that the six springs were in good category. The highest value of water quality index was at Taman Sari spring (88,48). The next highest value was at Beji Jeleka spring (86,87). Tirta Sudamala spring, Beji Kengetan spring, Gerembeng Kengetan spring and Rijasa spring have a value of water quality index 86,12; 84,29; 81,66 and 85,83.